RADIKALISME POLITIK KEAGAMAAN DI JAWA TENGAH - Mursid Zuhri (JURNAL LITBANG PROVINSI JAWA TENGAH, 2017)
The emergence of the view that followed the movement to change the state ideology of the Pancasila state into an Islamist state in one sense, and the reality of pluralist Indonesian population in other respects, often presents anxiety and concern about the emergence of both latential and expressive conflicts in various regions of Central Java. The subject matter of the study is essentially how the characteristics of the views followed by the radical movements, what is the background, in which the fertile lands of the growth of radicalism, and how to treat and anticipate the emergence of the radical movement. For the purpose of understanding these problems, qualitative studies were conducted on various views and movements that led to the characteristics of radicalism towards a number of informants in Surakarta, Wonosobo, Banyumas, Tegal, Pekalongan and Jepara. From the field findings, the background of the emergence of this radicalist movement is that religious sacred texts (Al Qur'an and Hadith) are open, literal and contextual, so as to raise various religious groups (moderate, radical, fundamentalist, etc.) which ultimately giving birth in group and out feeling group and unilateral evaluation. There is often an overlap between religious interests and the interests of religious communities. The fact shows that religion is capable of evoking the deepest emotions is often used as a tool of social mobilization. Violence with religious packaging becomes very possible. Selected fighting models are related to religious imagery, cultural community domination, the strength of social support and the role of the media. Efforts to prevent or exit that can be taken by: government policies should side with the weak, as well as fair treatment for every citizen before the law, the government must begin to open and open up for communication to solve national problems in a participatory, religious leaders must begin to set a good and consistent example, the need for awareness to all components that Indonesia is a pluralistic country.